Study of the current and proposed status of wheat cultivation and production in the Kingdom of Saudi Arabia - Adel M. Ghanem; Khalid N. Alrwis; Mohammad H. Alqunaibet; Othman S. Alnashwan; Abdul Aziz M. Alduwais; Sattam F. Almadrra; Sharafeldin B. Alaagib; Nageeb M. Aldwadahi (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
The research aimed to develop an economic plan to increase wheat production and reduce the amount of water used in water-stressed alluvial shelf areas, using quantitative economic analysis represented by the point estimation method and linear programming. This study showed that wheat production is concentrated in alluvial shelf areas, where the total relative importance of alluvial shelf production reached 84.69%, while the contribution of the Arabian Shield regions does not exceed 15.31% during the period 2018-2023. There is a disparity in wheat productivity between regions, as productivity ranged between a minimum of 4.09 tons/ha for the Jazan region and a maximum of 7.89 tons/ha for the Tabuk region. It was also shown that the priority areas for productive wheat cultivation are Al-Jouf, Tabuk, Qassim, Hail, Riyadh, and the Eastern Province. The proposed economic plan includes limiting wheat cultivation to Al-Jouf, Tabuk, Hail, and Makkah Al-Mukarramah regions. Accordingly, wheat production can be increased by 11.2% and the amount of water used in the alluvial shelf areas can be reduced by 6.27 million m3. The proposed plan also leads to an increase in the self-sufficiency rate for wheat from 25.3% to 28.1%. Finally, this study recommends the need to reconsider the wheat production policy, so that its cultivation is concentrated in areas with high productivity (Tabuk, Al-Jouf, Hail), and not in areas with low productivity (Madinah and Jazan).